Dietary supplementation and homocysteine levels and its effect on cardiovascular diseases - Korčok, Davor; Ćirić, Milan (Archives of Pharmacy, 2022)
Elevated homocysteine levels increases the risk of cardiovascular diseases. The aim of this study was to review the literature date on the mechanisms by which homocysteine promotes atherosclerosis and therefore the progression of cardiovascular diseases, as well as the benefits of dietary supplementation that affect the homocysteine levels, on patients’ general health. Review of a number of large studies suggested the mechanism of action and the effectiveness of dietary supplements on homocysteine levels. Recent studies showed that the intake of the active form of folic acid (5-methyltetrahydrofolate), vitamin D, vitamin C, vitamin B6 and vitamin B12 significantly reduces homocysteine levels in blood and therefore is recommended for lowering the risk of atherosclerosis and consequently coronary heart disease, stroke and blood vessels disorders. There are possible interventions capable of reducing homocysteine levels and therefore the risk of cardiovascular diseases. One of the therapeutic possibilities can be the use of dietary supplements. It was concluded that the elevation of homocysteine levels is associated with atherosclerosis which is mediated by its effect on oxidant stress mechanisms, vasodilatation process and on platelet adhesion and aggregation. Further research will be needed to determine its impact on cardiovascular diseases.